PROPHYLACTIC USE OF PROTHROMBIN COMPLEX CONCENTRATE VERSUS TRANEXAMIC ACID TO PREVENT MASSIVE OBSTETRIC HEMORRHAGE IN HIGH-RISK PREGNANCIES WITH LIVER CIRRHOSIS OR ITP - Ummatova R.Sh., Yusupov U.Yu. (Central Asian Journal of Medicine, 2025)
Postpartum hemorrhage (PPH) is a leading cause of maternal mortality worldwide [1]. International guidelines recommend early administration of tranexamic acid (TXA) during PPH to reduce bleeding [2]. However, pregnant women with liver cirrhosis or immune thrombocytopenic purpura (ITP) are at very high risk of severe hemorrhage, and the hemostatic defects of cirrhosis amplify this risk [3]. In cirrhosis, clotting factor deficiencies limit the effectiveness of TXA alone, since TXA stabilizes clots but does not replace missing factors. In this study we evaluated whether giving four-factor prothrombin complex concentrate (PCC) prophylactically before delivery would improve hemostasis and reduce bleeding more than standard TXA prophylaxis in these high-risk pregnancies. We conducted a two-part analysis (2019–2024). First, we retrospectively reviewed 79 high-risk deliveries (44 with cirrhosis, 35 with ITP) to characterize bleeding outcomes. Next, we performed a prospective trial in 70 cirrhotic women at delivery, comparing PCC prophylaxis (n=32) to standard TXA prophylaxis (n=38). Coagulation parameters (INR, APTT, fibrinogen, platelet count) were monitored, and clinical outcomes (total blood loss, transfusions, surgical interventions) were recorded. Retrospective data confirmed very high hemorrhage rates: mean blood loss 852 ml and surgical hemostasis needed in 47% of cases. In the prospective trial, PCC infusion rapidly normalized coagulation (INR and APTT fell significantly and fibrinogen rose), whereas TXA alone did not fully correct coagulopathy. Clinically, PCC prophylaxis markedly reduced bleeding: it lowered the risk of massive hemorrhage by roughly 3–5 times compared to TXA, and no patient in the PCC group required hysterectomy or developed fatal outcomes. Shock, disseminated intravascular coagulation, and transfusion requirements were significantly less frequent with PCC. Overall, maternal morbidity was greatly improved when PCC was used. Our findings demonstrate that prophylactic PCC before delivery produces stronger hemostatic correction and dramatically fewer hemorrhagic complications than TXA alone in cirrhotic pregnancies. This strategy markedly improved maternal survival and preserved uterine integrity, while reducing the need for expensive interventions. We recommend that obstetric management of very-high-risk patients (e.g. those with liver cirrhosis) include planned PCC replacement as an adjunct to standard care, to optimize maternal and fetal outcomes.